2017
DOI: 10.1177/2047487317715109
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular function in relation to chronic residential air pollution in a general population

Abstract: BackgroundIn view of the increasing heart failure epidemic and awareness of the adverse impact of environmental pollution on human health, we investigated the association of left ventricular structure and function with air pollutants in a general population.MethodsIn 671 randomly recruited Flemish (51.7% women; mean age, 50.4 years) we echocardiographically assessed left ventricular systolic strain and strain rate and the early and late peak velocities of transmitral blood flow and mitral annular movement (200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 62 publications
0
28
1
Order By: Relevance
“…1 Previous studies observed cardiovascular-related health effects, like subclinical changes in left ventricular performance, most likely caused by decreased ventricular function in response to PM 2.5 exposure. 35 Although still lacking a complete understanding of the health effect mechanisms, our findings can be linked to the public health risk of air pollution and road traffic noise on cardiovascular health. 36 Lacking safe levels of air pollutants, large parts of the population may be subjected to these adverse environmental effects on the vasculature, especially when not given personal risk (e.g.…”
Section: Discussionmentioning
confidence: 90%
“…1 Previous studies observed cardiovascular-related health effects, like subclinical changes in left ventricular performance, most likely caused by decreased ventricular function in response to PM 2.5 exposure. 35 Although still lacking a complete understanding of the health effect mechanisms, our findings can be linked to the public health risk of air pollution and road traffic noise on cardiovascular health. 36 Lacking safe levels of air pollutants, large parts of the population may be subjected to these adverse environmental effects on the vasculature, especially when not given personal risk (e.g.…”
Section: Discussionmentioning
confidence: 90%
“…Another benefit of using AOD in <10 km 2 grids is the possibility of replacing ZIP-code-aggregated health data with address-level health data [23,30,[88][89][90][91]. Patient privacy issues require obtaining the patient's written consent before using a person's ED visit or IP hospitalization record in an environmental health epidemiologic study.…”
Section: Discussionmentioning
confidence: 99%
“…(1)(2)(3) High air particulate matter (PM) levels have repeatedly been linked to the occurrence of fatal and non-fatal acute cardiovascular events. (4)(5)(6) Approximately one half on cardiovascular deaths are due to out-of-hospital cardiac arrests (OHCA), which are defined as the cessation of cardiac mechanical activity occurring outside the hospital. OHCA is characterized by a poor prognosis and very high mortality.…”
Section: Introductionmentioning
confidence: 99%